DIGITAL CRIME AND POLICE RESPONSE IN NIGERIA: INSTITUTIONAL CHALLENGES AND SECURITY IMPLICATIONS - Akinola Osho, Osaretin (African Journal of Social and Behavioural Sciences, 2025)
This study examines the intersection of digital transformation and the challenges facing the Nigeria Police Force (NPF) in addressing digital-related crimes and their broader implications for national security. The study employed the qualitative approach. Data for the study was collected through primary sources, including key informant interviews (KIIs) and in-depth interviews (IDIs) and other secondary sources such as books, journals and media reports. Based on the Situational Crime Prevention (SCP) theoretical framework, findings show that the NPF’s limitations stem from inadequate funding, poor digital infrastructure and equipment, institutional decay, and insufficient training. Although government efforts such as establishing digital literacy centres, initiating training and retraining programs, and partnering with local and international agencies represent steps in the right direction, their effectiveness is often undermined by systemic corruption and institutional weaknesses. These challenges have serious implications for national security. The study emphasises the urgent need to address these barriers, with particular attention to sustained political will and increased investment in the sector.